Spontaneous bacterial peritonitis in patients with cirrhosis: incidence, outcomes, and treatment strategies - Marciano, Sebastián; Díaz, Juan Manuel; Dirchwolf, Melisa; Gadano, Adrián (Hepatic Medicine : Evidence and Research, 2019)
Spontaneous bacterial peritonitis is the most frequent bacterial infection in patients with cirrhosis. The reported incidence varies between 7% and 30% in hospitalized patients with cirrhosis and ascites, representing one of their main ...